Urine specific gravity as a diagnostic tool for dehydration in children - Kalis Joko Purwanto; Mohammad Juffrie; Djauhar Ismail (Indonesian Pediatric Society, 2010)
Background Using clinical judgment to diagnose dehydration can be highly subjective. To diagnose dehydration, it would be ideal to have an accurate, inexpensive, objective and easy-to-perform diagnostic tool. In cases of dehydration, plasma osmolality rises, causing an increase in antidiuretic hormone (ADH) secretion. The increased ADH reduces urine production and increases urine osmolality. Previous studies have show that urine osmolality correlates well to urine specific gravity. We investigated if urine specific gravity can be a reliable and objective detennination of dehydration status.Objective To assess the accuracy of using urine specific gravity as a diagnostic tool to determine dehydration status of children with diarrhea.Methods We conducted the study in the pediatric ward of Sardjito Hospital from September 2009 to December 2009. Using a refractometer we measured urine specific gravity from patients with diarrhea. This measurement was then compared to a standard of acute body weight loss, with dehydration defined as weight loss of 5% or more. The cut-off value for defining dehydration using specific gravity measurements was detennined by a receiver-operator curve (ROC).Results Out of 61 pediatric patients who were recruited in this study, 18 (30%) had dehydration as defined by a body weight loss of 5% or more. Based on the ROC, we determined the cut offÂ value for urine specific gravity to be 1.022. Using this value, urine specific gravity was 72% sensitive (95% CI 52 to 93), and 84% specific (95% CI 73 to 95) in determining dehydration status.Conclusion Urine specific gravity is less accurate than clinical judgment in determining dehydration status in children with diarrhea.